Revisiting Subject–Object Asymmetry in the Production of Cantonese Relative Clauses: Evidence From Elicited Production in 3-Year-Olds - Chan, Angel; Matthews, Stephen; Tse, Nicole; Lam, Annie; Chang, Franklin; Kidd, Evan (Frontiers in Psychology, 2021)
Emergentist approaches to language acquisition identify a core role for language-specific experience and give primacy to other factors like function and domain-general learning mechanisms in syntactic development. This directly contrasts with nativist structurally-oriented approach, which predicts that grammatical development is guided by Universal Grammar and that structural factors constrain acquisition. Cantonese relative clauses (RCs) offer a good opportunity to test these perspectives because its typologically rare properties decouple the roles of frequency and complexity in subject- and object- RCs in a way not possible in European languages. Specifically, Cantonese object RCs of the classifier type are frequently attested in children’s linguistic experience and are isomorphic to frequent and early-acquired simple SVO transitive clauses, but according to formal grammatical analyses Cantonese subject RCs are computationally less demanding to process. Thus, the two opposing theories make different predictions: the emergentist approach predicts a specific preference for object RCs of the classifier type, whereas the structurally-oriented approach predicts a subject advantage. In the current study we revisited this issue. Eighty-seven monolingual Cantonese children aged between 3;2 and 3;11 (Mage: 3;6) participated in an elicited production task designed to elicit production of subject- and object- RCs. The children were very young and most of them produced only noun phrases when RCs were elicited. Those (9 children) who did produce RCs produced overwhelmingly more object RC than subject RCs, even when animacy cues were controlled. The majority of object RCs produced were the frequent classifier-type RCs. The findings concur with our hypothesis from the emergentist perspectives that input frequency and formal and functional similarity to known structures guide acquisition.